As estratégias e a organização das indústrias de farinha de trigo e de massas alimentícias do Rio Grande do Sul - Dalla Corte, Vitor Francisco (2008)
The study aims to identify the strategies and the organization of the wheat flour industries and nutritious pastes of Rio Grande do Sul. It is used as theoretical base in the analysis, the production chain, the model structure-conduct-performance (SCP) and Porter s (1980) and Mintzberg s (1988) competitive strategies. In order to accomplish the research the descriptive method was used, with primary (structured questionnaire applied to the companies) and secondary data. The option of restricting the study to Rio Grande do Sul, was due to the fact that the state to be one of the pioneers and now one of the largest producers of wheat flour and nutritious pastes in the country. The results show that the wheat flour industries and of nutritious pastes are located close to one another in the state most them are of medium and small-size companies. It was also observed that both Brazil and Rio Grande do Sul are not self-sufficient in the wheat production thus, making the importation necessary. The main destination to products is the state itself, but the vertical integration in the productive chain is still low. It was also verified that the concentration of the industries falls from 2001 to 2006 and that there are barriers to the important entrance for the incoming in the wheat flour sector, as the minimum scale of production, and the capacity already installed of the companies producing nutritious pastes. Concerning Porter s competitive strategies, the production with lower costs is the most outstanding among the companies producing wheat flour, however, among the nutritious pastes it is the differentiation. Among the Mintzberg s typologies, the quality of the product is considered, by both industries, as being the big competitive differential. The performance of the industries in the analyzed period worsened, because there was profitability decrease and market share loss.